Cerebrospinal fluid proteomic profiling of individuals with mild cognitive impairment and suspected non‐Alzheimer's disease pathophysiology. Issue 3 (14th June 2022) - Delvenne, Aurore; Gobom, Johan; Tijms, Betty; Bos, Isabelle; Reus, Lianne M.; Dobricic, Valerija; Kate, Mara ten; Verhey, Frans; Ramakers, Inez; Scheltens, Philip; Teunissen, Charlotte E.; Vandenberghe, Rik; et al.
Abstract: Background: Suspected non‐Alzheimer's disease pathophysiology (SNAP) is a biomarker concept that encompasses individuals with neuronal injury but without amyloidosis. We aim to investigate the pathophysiology of SNAP, defined as abnormal tau without amyloidosis, in individuals with mild cognitive impairment (MCI) by cerebrospinal fluid (CSF) proteomics. Methods: Individuals were classified based on CSF amyloid beta (Aβ)1‐42 (A) and phosphorylated tau (T), as cognitively normal A—T– (CN), MCI A–T+ (MCI‐SNAP), and MCI A+T+ (MCI‐AD). Proteomics analyses, Gene Ontology (GO), brain cell expression, and gene expression analyses in brain regions of interest were performed. Results: A total of 96 proteins were decreased in MCI‐SNAP compared to CN and MCI‐AD. These proteins were enriched for extracellular matrix (ECM), hemostasis, immune system, protein processing/degradation, lipids, and synapse. Fifty‐one percent were enriched for expression in the choroid plexus. Conclusion: The pathophysiology of MCI‐SNAP (A–T+) is distinct from that of MCI‐AD. Our findings highlight the need for a different treatment in MCI‐SNAP compared to MCI‐AD.